Study on Potential of Clay Brick Industry Waste as Replacement of Aggregate in Concrete - Megat Mohd, Wan Nurnazura; Ahmad Jeni, Mohamad Luthfi (Progress in Engineering Application and Technology, 2021)
Many ways that can be used to produce such a strong and long lasting use of concrete. This is because many country have been facing with the problem of tons of Construction and Demolition Waste (CDW) and Malaysia also is one of the listed country. From the previous study, it is proved that using brick aggregate as alternative aggregates can also reduce natural aggregate consumption, concrete density, and most important is being considered as the environmentally friendly approach. Therefore, for this study, clay brick waste will be used as the replacement of aggregate in concrete. The aim for this research is to discover the mechanical properties and the potential use of the clay brick industry waste as a replacement of aggregate in concrete. The mechanical properties that will be reviewed the most are the workability of the concrete, compressive strength and water permeability of the concrete. All the data and information are extracted from previous research papers. It is proven that different percentage replacement of aggregate into the concrete will give different mechanical performance of the concrete. Generally, up to 50% of the aggregate percentage replacement is acceptable, but still, natural aggregate presented as the best mechanical performance in concrete.